Pederasts and Others : Urban Culture and Sexual Identity in Nineteenth-Century Paris. - Dececco, Phd, John (Haworth gay & lesbian studies., 2012)
Examine how a community of support in Nineteenth-Century Paris became a blueprint for modern sexual identity! A unique social history, Pederasts and Others: Urban Culture and Sexual Identity in Nineteenth-Century Paris is a valuable addition to the growing field of gay and lesbian studies. The book examines the interaction between the city's male homosexual subculture and Parisian authority figures who attempted to maintain political and social order during the early years of the French Third Republic by using laws against public indecency and sexual assault to treat same-sex sexuality as a cr.